Carbon footprint and embodied energy assessment of roof-covering materials - Duong Le, A.; Whyte, Andrew; Biswas, Wahidul (Springer, 2018)
The residential building sector regularly satisfies a diverse range of housing needs whilst addressing respective capital-cost considerations. Designers and builders must also be aware of the environmental implications of their design specifications; the work here adds to a body of knowledge concerned with carbon footprint and embodied energy demand, specifically through an examination of alternative roof-covering materials. A life cycle assessment (LCA) has been carried out, within a West Australian context, to compare impacts for the roof specification options of: clay tile; concrete tile; and sheet metal. In locations where recycling facilities are unavailable and thus disregarded, it is found that clay tiles have the lowest carbon footprint of 4.4 t of CO2 equivalent (CO2e-) and embodied energy demand of 52.7 Mega Joule (MJ) per 100 m2, while sheet-metal roofing has the highest carbon footprint (9.85 t of CO2e-), with concrete roof tiles having the highest embodied energy demand (83 MJ). Findings confirm that a sheet-metal roof can obtain significant carbon and embodied energy saving benefits (i.e. 71–73%) compared to clay tile or concrete roof covers through ongoing encouragement of recycling strategies and increased local recycling facilities able to embrace residual cradle-to-cradle material reuse